Gamow-Teller strength and beta-decay rate within the self-consistent deformed pnQRPA. Issue 1 (January 2016) - Martini, M; Goriely, S; Péru, S
Abstract: In recent years fully consistent quasiparticle random-phase approximation (QRPA) calculations using finite range Gogny force have been performed to study electromagnetic excitations of several axially-symmetric deformed nuclei up to the 238 U. Here we present the extension of this approach to the charge-exchange nuclear excitations (pnQRPA). In particular we focus on the Gamow-Teller (GT) excitations which are known to play a crucial role in several fields of physics, in particular in nuclear astrophysics (stellar evolution and nucleosynthesis). A comparison of the predicted GT strength distribution with existing experimental data is presented. The role of nuclear deformation is shown. Special attention is paid to β-decay halflives calculations for which experimental data exist and for specific isotonic chains of relevance for the r-process nucleosynthesis.